Ten questions concerning a new adolescent health urbanism - Knöll, Martin; Roe, Jennifer J. (Building and environment, 2017)
This article sets out an urban health model and conceptual framework for researching environments that support adolescent health and wellbeing. Our focus is on 10–19 year olds, an age group that has been neglected by researchers in the otherwise emerging and dynamic field of design and health over the past decade. The Ten Questions address adolescent urban lifestyles and their relation to health outcomes in Europe, adolescent perceptions of the built environment and age specific physical, social, digital and emotional affordances as well as, addressing how to increase participation of adolescents in health-oriented urban design processes. A model of adolescent health urbanism is introduced that integrates place and person characteristics in a dynamic model that addresses everyday practices across the adolescent age span. Based on a review of the evidence from urban planning and environmental psychology literature, this article emphasises the need for a more adolescent-responsive urban design process, the need for more research into age-specific urban affordances; integration of new technologies to forge mobility in and engagement with in the co-design of cities allowing stakeholders to make better-informed planning decisions. •A new adolescent health urbanism can help address major health challenges including mental wellbeing and physical activity.•The model integrates aspects of the self with urban place attributes, together with adolescents' “everyday practices” to build health and wellbeing.•The model considers the dynamic periods of transition within adolescence (e.g. primary to secondary school, and to higher education and the workforce).•Understanding health and wellbeing from the perspective of what matters to adolescents - combined with co-design - is critical to these new approaches.